Dysregulation of the histone demethylase KDM6B in alcohol dependence is associated with epigenetic regulation of inflammatory signaling pathways. (1st August 2019) - Johnstone, Andrea L.; Andrade, Nadja S.; Barbier, Estelle; Khomtchouk, Bohdan B.; Rienas, Christopher A.; Lowe, Kenneth; Van Booven, Derek J.; Domi, Esi; Esanov, Rustam; Vilca, Samara; Tapocik, Jenica D.; Rodriguez, Keli; et al.
Abstract: Epigenetic enzymes oversee long‐term changes in gene expression by integrating genetic and environmental cues. While there are hundreds of enzymes that control histone and DNA modifications, their potential roles in substance abuse and alcohol dependence remain underexplored. A few recent studies have suggested that epigenetic processes could underlie transcriptomic and behavioral hallmarks of alcohol addiction. In the present study, we sought to identify epigenetic enzymes in the brain that are dysregulated during protracted abstinence as a consequence of chronic and intermittent alcohol exposure. Through quantitative mRNA expression analysis of over 100 epigenetic enzymes, we identified 11 that are significantly altered in alcohol‐dependent rats compared with controls. Follow‐up studies of one of these enzymes, the histone demethylase KDM6B, showed that this enzyme exhibits region‐specific dysregulation in the prefrontal cortex and nucleus accumbens of alcohol‐dependent rats. KDM6B was also upregulated in the human alcoholic brain. Upregulation of KDM6B protein in alcohol‐dependent rats was accompanied by a decrease of trimethylation levels at histone H3, lysine 27 (H3K27me3), consistent with the known demethylase specificity of KDM6B. Subsequent epigenetic (chromatin immunoprecipitation [ChIP]–sequencing) analysis showed that alcohol‐induced changes in H3K27me3 were significantly enriched at genes in the IL‐6 signaling pathway, consistent with the well‐characterized role of KDM6B in modulation of inflammatory responses. Knockdown of KDM6B in cultured microglial cells diminished IL‐6 induction in response to an inflammatory stimulus. Our findings implicate a novel KDM6B‐mediated epigenetic signaling pathway integrated with inflammatory signaling pathways that are known to underlie the development of alcohol addiction. Abstract : Through quantitative mRNA expression analysis of over 100 epigenetic enzymes, we identified 11 that are dysregulated in the brain of alcohol dependent rats. The histone 3, lysine 27 (H3K27me3) demethylase KDM6B, was found to have region‐specific dysregulation in the prefrontal cortex and nucleus accumbens and also in human alcoholic brain tissues. A ChIP‐sequencing analysis showed that alcohol‐induced changes in H3K27me3 were enriched at genes in the IL‐6 signaling pathway, thereby implicating a novel KDM6B‐mediated epigenetic signaling pathway integrated with inflammatory signaling pathways that underlie alcohol addiction.